Candida colonisation in asymptomatic HIV patients attending a tertiary hospital in Benin City, Nigeria - Esebelahie, Newton O. (Co-Action Publishing, 2013)
BACKGROUND: Candidiasis is the commonest opportunistic fungal infection in patients infected with human immunodeficiency virus (HIV). CD4+ lymphocyte counts have been found to be a marker of HIV disease progression. AIM: This study focused on determining the spectrum of Candida isolates in urine, stool, and oral specimens among HIV patients in a tertiary hospital. METHODS: A total of 300 subjects comprising of 200 HIV patients and 100 non-HIV subjects were used for this study. Three samples (urine, stool, and oral swab) were collected from each subject. Each specimen was processed using standard microbiological techniques and emergent Candida isolates were identified with CHROMagar™ Candida and sugar fermentation tests. RESULTS: The overall prevalence of Candida colonisation among HIV patients was 52.5%. HAART-naive patients had a significantly higher prevalence (OR = 3.65; 95% CI = 2.03–6.56; p<0.0001) than their counterpart on highly active antiretroviral therapy (HAART) (OR = 1.99; 95% CI = 1.13–3.50; p=0.0232). Female gender was a significant risk factor for acquiring Candida infection (OR = 3.40; 95% CI = 1.14–10.13; p=0.0289). The effect of age on prevalence of candidiasis was observed among HIV patients on HAART (p=0.0161). A CD4+ count <200 cells/µl was a significant risk factor for acquiring candidal infection only among HAART-naive patients (OR = 4.37; 95% CI = 1.60–11.95; p=0.0042). The five species of Candida recovered from this study were C. albicans, C. krusei, C. parapsilosis, C. tropicalis, and C. glabrata. CONCLUSION: There is a significant relationship between antiretroviral therapy, CD4+ counts, and the prevalence of candidiasis.